Indoor and Outdoor Exposure to PM2.5 during COVID-19 Lockdown in Suburban Malaysia - Eliani Ezani; Peter Brimblecombe; Zulfa Hanan Asha’ari; Amirul Aiman Fazil; Sharifah Norkhadijah Syed Ismail; Zamzam Tuah Ahmad Ramly; Md Firoz Khan (Aerosol and Air Quality Research)
Abstract During the COVID-19 pandemic, key policies aimed at reducing exposure to the virus from social distancing, restrictions on travel through to strongly enforced lockdowns. However, COVID-19 restrictions required people to spend more time at home so the exposure to air pollutants shifted to being derived from that of domestic interiors, rather than outdoors or the workplace environment. This study aims to characterise the influence of lockdown intervention on the balance of indoor and outdoor PM2.5 exposure in a Malaysian suburb. We also calculate the potential health risk from exposure to both indoor and outdoor PM2.5 to give context to personal exposure assessment in different microenvironments during the COVID-19 lockdown, known locally as Movement Control Orders (MCO). The implementation of the MCOs slightly reduced daily average of outdoor PM2.5 concentrations (median of 12.63 µg m–3 before and 11.72 µg m–3). In the Malaysian apartment considered here, cooking led to a substantial increase in exposure from increasing concentrations in PM2.5 during a COVID-19 lockdown (maximum average concentration at 52.2 µg m–3). The estimated excess risk to health was about 25% for lung cancer from staying indoor. Thus, there seems a potential for greater exposure to fine particles indoors under lockdown, so it is likely premature to suggest that more lives were saved through a reduction of outdoor pollutants than lost in the pandemic. Unfortunately, little is known about the toxicity of indoor particles and the types of exposures that result where people increase the amount of time they spend working from home or staying indoors, especially during periods of lockdown.